Exclusive Image Gallery on Human Spinal Cord Regeneration-Clinical Image-1 - Giselher Schalow (Imaging Journal of Clinical and Medical Sciences - Peertechz Publications, 2019)
A. Spinal cord segments and their relation to the vertebral bodies. Note the Ascensus of the spinal cord, giving rise to the long cauda equina nerve roots. B. Approximate segmental innervation of the skin. C. Below the spinal cord injury level there is loss of sensitivity and loss of connectivity to muscle and other functions.